Exploratory analysis of internet search trends during the COVID-19 outbreak - Aquino Canchari, Christian Renzo (2020)
Coronavirus disease 2019 has put the world in a health emergency. Searching for information on the Internet largely reflects people's interest in this pandemic. Objective: Conduct an exploratory analysis of Internet search trends during the 2019 coronavirus disease outbreak. Methods: Google Trends was used to provide data on the relative volume of Google searches for terms related to 2019 coronavirus disease. The evaluation period was from January 01 to May 17, 2020. Results: The search term used to know this pandemic was “coronavirus”, the most searched symptom was “fever”, followed by “sore throat” and “cough”, in addition, the interest of users to know the transmission routes of the acute respiratory syndrome coronavirus 2. As for preventive measures, the most searched term was “stay home”, followed by “facial masks”, “social distancing” and “washing hands”. Conclusions: The results confirmed interest in COVID-19 via Internet. Using information from people's Internet search interest could help formulate health policies to better control the 2019 coronavirus disease outbreak.